Paisagem sonora e criação musical contemporânea : o processo composicional em instâncias - Silva, Nelsindo de Moraes da (2012)
This research aims to describe the process of musical creation of Instâncias (Instances), trying to extend the matter for soundscape and composition relations. The musical construction has had as references the sound objects (SCHAEFFER, 1993) present in the soundscape (SCHAFER, 1991) from the city of Cuiabá, perceived as generating images (SALLES, 2004) for creating. To this objective, audio recordings have done in four environments correlated with aspects of human existence ─ developed from the reading of contemporary thinkers such as Zygmunt Bauman, Michel Maffesoli, Mircea Eliade, Marc Augé and Massimo Canevacci – respectively: the urban center (squares and sidewalks), concerning to the mobility; the production sector of an industry for the work dimension; the food court of a shopping center, linked it to pleasure and, at last, religious temples, connected them to spirituality. Thus, it is considered that the sound texture, emanating from these realities, manifests itself like a synthesis of the dimensions, which permeate the existence. For data processing (listening process, registration and classification), the theory of Pierre Schaeffer (1993), about the reduced listening and the sound object, has applied. The objects have recorded and classified on the traditional musical notation as references system; expressed in motifs (melodic and rhythmic), establishing them as postulations of creative process. Instâncias was composed for a chamber orchestra, in four movements, they are: Mobility (1st Movement), Work (2nd Movement), Hedonic (3rd Movement) and Spiritual (4th Movement).